Features of conservative therapy of benign prostatic hyperplasia in patients with metabolic syndrome: " Treat to Target " - V. B. Filimonov; P. V. Vasin; V. N. Panchenko (Исследования и практика в медицине)
Purpose of the study. To improve the results of treatment of benign prostatic hyperplasia with symptoms of the lower urinary tract in the presence of concomitant metabolic syndrome.Materials and methods. The investigation included 103 patients aged 42 to 75 years with a reliable diagnosis of BPH and signs of MS, according to the criteria of GFCF (2009). Patients were randomized into two comparable groups: Group 1 included 52 men who were prescribed tamsulosin in combination with targeted correction of metabolic disorders; Group 2 consisted of 51 men who were prescribed tamsulosin monotherapy. After 6 and 12 months of the study, the dynamics of metabolic parameters, prostate volume, residual urine volume, maximum urine flow rate, and total IPSS and QoL score were evaluated in each group of patients.Results. A direct correlation was established between the severity of metabolic disorders and the progression of BPH /LUTS in the main assessed indicators. The use of combination therapy with metformin, ACE inhibitors / ARA and statins in combination with tamsulosin showed efficacy after 6 and 12 months of the study compared with tamsulosin monotherapy. The treatment is based on the rinciple of T2T ("Treat to Target"): maintaining target levels of blood pressure, glucose, blood lipid parameters, and body weight correction.Conclusion. Overweight, arterial hypertension, the atherogenic profile of dyslipidemia and hyperglycemia are risk factors for more pronounced progression of BPH / LUTS and a deterioration in the quality of life of patients. The investigation IMSYPA showed the effectiveness of pathogenetically based complex therapy aimed at eliminating metabolic imbalance.